A novel strategy to simultaneously enhance bio-oil yield and nutrient recovery in sequential hydrothermal liquefaction of high protein microalgae. (1st March 2022) - Chen, Jie; Zhang, Jing; Pan, Wei; An, Guojun; Deng, Ying; Li, Yingjie; Hu, Yicheng; Xiao, Yu; Liu, Tonggui; Leng, Songqi; Chen, Jiefeng; Li, Jun; et al.
Graphical abstract: Highlights: Bio-oil yield increased from 16% to 28.65% in SEQ-HTL with SII-AP recycling. 33–53% C in SII-AP were recovered and transferred into SII-Oil and SII-Char. Maillard, Michael addition and acylation reactions were key pathways of bio-oil increase. Replacing medium nutrients with SI-AP was feasible for fungal-algal cultivation. Abstract: Advances in sequential hydrothermal liquefaction (SEQ-HTL, or two-step HTL) is limited by its low bio-oil production and enormous aqueous phase (AP) byproduct. The objective of this study was to integrate AP recirculation and fungal-microalgal cultivation with the SEQ-HTL to simultaneously improve bio-oil yield, energy recovery, and nutrient recovery. Specifically, AP from the first step (SI-AP) of SEQ-HTL was used to culture microalgae and fungi for nutrient recovery, and AP from the second step (SII-AP) was recycled four times as reaction solvent to enhance bio-oil yield. Interestingly, the SI-AP showed excellent biodegradability, and the complementary cultivation of fungi and algae has tremendous potential to recover nutrients. For example, 0.96 g/L fungi biomass and 87.71% chemical oxygen demand (COD) removal rate were obtained by fungi cultivation in SI-AP, and 1.35 g/L biomass and 63.80% ammonia nitrogen (NH4 -N) removal rate were received by microalgae cultivation in SI-AP. The difference of dissolved organic matter in SI-AP and the AP from conventional HTL (HTL-AP, inhibited microalgae significantly) pointed out unsaturated substances and lignins/carboxylic-rich alicyclic molecules substances might be the primary factor inhibiting microalgae growth. During SII-AP recirculation, the yields of bio-oil (SII-Oil) and hydrochar (SII-Char) increased from 16.00% to 28.65% and 2.93% to 5.66%. 32.96–53.08% C and 15.93–24.00% N in SII-AP were recovered and transferred into SII-Oil and SII-Char. A series of characterizations showed that the increased bio-oil formation was mainly the transformation of amines, glycerol, alcohols, acetic acid, and amino acid fragments from the AP into the oil phase via Maillard reaction, Michael addition reaction and acylation. Overall, the novel strategy could improve the economic feasibility of processing high-protein microalgae biomass using the SEQ-HTL technique and is promising to the industrial applications of microalgae.